Enculturation of Bugis Sidenreng Rappang Local Wisdom through Ethnopedagogy of Traditional Games - Adela, Dhea; Suastra, I Wayan; Lasmawan, I Wayan (International Journal of Elementary Education, 2023)
Efforts to preserve local culture face challenges with the domination of foreign cultural acculturation which is starting to dominate today. The actualization of local wisdom values ​​through traditional games is a potential for the development of the sociological-anthropological basis of the curriculum in schools. Such as traditional games which are still preserved by the local Bugis Sidenreng Rappang community, South Sulawesi. The purpose of this study was to analyze the values ​​of local wisdom contained in traditional games of the Bugis tribe to then become the sociological- anthropological foundation of education. This research approach uses a qualitative approach with a phenomenological design. Data analysis used interpretative phenomenological analysis. These traditional games include Massempe, Maraga, Maggasing, Maggalenceng, Massantok, Mallogo, Maggale, and Mappasajang. Data collection techniques using observation, interviews, and documentation. The results of the study show that each traditional game that is played has an attitude and social value that can be used as curriculum development based on local wisdom such as malempu (honest), warani (brave), never give up, conscientious, creative, cooperative, and practice in problem solving. This age-old Bugis game is brimming with moral principles. The character education of students in schools is strengthened by playing traditional games. This is evident in a number of areas of people's life, including those related to education, society, the economy, and health.